Perilaku Cyberbullying yang Terjadi pada Siswa di SMA Taman Siswa Padang - Hendriani, Yuliza; Sukmawati, Indah (Lembaga Yasin AlSys, 2023)
This research is motivated by the phenomenon of cyberbullying behavior at school. Where this can have a negative effect on the student's personal quality and quantity. This research aims to describe the picture of cyberbullying in terms: (1) flaming, (2) harassment, (3) denigration, (4) impersonation, ( 5) outing & trickery, (6) exclusion, (7) cyberstalking. This type of research uses a quantitative approach with research methods, namely descriptive methods. The population of this study was 55 students, classes X, XI, The instrument used was a questionnaire with a Likert scale model. The data analysis technique uses descriptive analysis techniques. Based on the research findings, namely, (1) cyberbullying behavior in students seen from the flaming aspect is in the high category, (2) cyberbullying behavior in students seen from the harassment aspect is in the medium category, (3) cyberbullying behavior in students seen from the denigration aspect is in the medium category, (4) cyberbullying behavior among students seen from the impersonation aspect is in the high category, (5) cyberbullying behavior among students seen from the outing & trickery aspect is in the medium category, (6) cyberbullying behavior among students seen from the exclusion aspect is in the medium category, (7) cyberbullying behavior among students seen from the cyberstalking aspect is in the high category. The implications of guidance and counseling in the form of information services can provide various information regarding tendencies in cyberbullying behavior. Group guidance services with material on